Monitoring microseismicity of the Hengill Geothermal Field in Iceland - Grigoli, Francesco; id_orcid:0 000-0002-2858-9756; Clinton, John Francis; id_orcid:0 000-0001-8626-2703; Diehl, Tobias; id_orcid:0 000-0001-6264-1506; Kaestli, Philipp; Scarabello, Luca; Agustsdottir, Thorbjorg; Kristjansdottir, Sigridur; Magnusson, Rognvaldur; Bean, Christopher J.; et al. (Nature, 2022)
Induced seismicity is one of the main factors that reduces societal acceptance of deep geothermal energy exploitation activities, and felt earthquakes are the main reason for closure of geothermal projects. Implementing innovative tools for real-time monitoring and forecasting of induced seismicity was one of the aims of the recently completed COSEISMIQ project. Within this project, a temporary seismic network was deployed in the Hengill geothermal region in Iceland, the location of the nation's two largest geothermal power plants. In this paper, we release raw continuous seismic waveforms and seismicity catalogues collected and prepared during this project. This dataset is particularly valuable since a very dense network was deployed in a seismically active region where thousand of earthquakes occur every year. For this reason, the collected dataset can be used across a broad range of research topics in seismology ranging from the development and testing of new data analysis methods to induced seismicity and seismotectonics studies. ISSN:2052-4463